Airborne radar imaging of subaqueous channel evolution in Wax Lake Delta, Louisiana, USA. Issue 10 (17th May 2016) - Shaw, John B.; Ayoub, Francois; Jones, Cathleen E.; Lamb, Michael P.; Holt, Benjamin; Wagner, R. Wayne; Coffey, Thomas S.; Chadwick, J. Austin; Mohrig, David
Abstract: Shallow coastal regions are among the fastest evolving landscapes but are notoriously difficult to measure with high spatiotemporal resolution. Using Uninhabited Aerial Vehicle Synthetic Aperture Radar (UAVSAR) data, we demonstrate that high signal‐to‐noise L band synthetic aperture radar (SAR) can reveal subaqueous channel networks at the distal ends of river deltas. Using 27 UAVSAR images collected between 2009 and 2015 from the Wax Lake Delta in coastal Louisiana, USA, we show that under normal tidal conditions, planform geometry of the distributary channel network is frequently resolved in the UAVSAR images, including 700 m of seaward network extension over 5 years for one channel. UAVSAR also reveals regions of subaerial and subaqueous vegetation, streaklines of biogenic surfactants, and what appear to be small distributary channels aliased by the survey grid, all illustrating the value of fine resolution, low noise, L band SAR for mapping the nearshore subaqueous delta channel network. Key Points: Remote sensing of rapidly evolving river delta bathymetry is limited by turbid water UAVSAR images resolve the subaqueous channel network through variation in water surface roughness UAVSAR time series resolves small incipient channels and 700 m of channel network extension